A search for justice using AI-assisted image creation - Lucy Van Sambeek (International Journal of Narrative Therapy and Community Work, 2024)
As artificial intelligence becomes pervasive, therapists might be left wondering about its implications for narrative practice. This paper explores an unexpected discovery about the power of artificial intelligence in re-imagining a story of injustice. Lucy (the therapist) and Miles (the client) used an AI image creator to assist in the externalisation of problems. Creating imagery representing Miles’s story of injustice and sharing the images with outsider witnesses became acts of justice and healing. The process of narrative justice using AI has implications for the practice of narrative therapy. This article finishes with an opportunity for readers and viewers to respond to Miles’s online gallery of imagery.